PKM2-mediated STAT3 phosphorylation promotes acute liver failure via regulating NLRP3-dependent pyroptosis - Songman Yu; Siya Pei; Min Zhang; Shang Gao; Jun Chen; Lihua Duan; En Hu; Yang Wang; Yan Huang (Communications Biology)
Abstract Acute liver failure (ALF) is a life-threatening clinical syndrome characterized by high-grade inflammation and multi-organ failure. Our previous study shows that targeting the M2 isoform of pyruvate kinase (PKM2) to inhibit macrophage inflammation may be a promising strategy for ALF treatment. however, the mechanism by which PKM2 regulates the inflammatory response is unclear. Here we demonstrate that PKM2 contributes to ALF by modulating NLRP3-mediated pyroptosis activation in liver macrophages. The specific knockout of PKM2 in myeloid cells reduces mortality and alleviates hepatic injury in D-galactosamine/LPS-induced ALF mice. Single-cell transcriptome analysis suggests that NLRP3 inflammasome activation of macrophages involves in ALF, knockout of PKM2 in macrophages reduces the expression of NLRP3, and activation of pyroptosis. Pharmacological inhibition of the PKM2 nuclear translocation, but not glycolytic activity, protects mice from ALF. Pharmacological and genetic inhibition of PKM2 attenuates NLRP3-mediated pyroptosis activation and consequently reduces the release of IL-1β and IL-18 by macrophages. Mechanistically, PKM2 translocates into the nucleus and combines with STAT3, enhancing its phosphorylation and recruitment to the NLRP3 promoter region, thereby increasing NLRP3 expression. This work defines PKM2 acts as an important nonmetabolic regulator of NLRP3 that modulates pyroptosis activation in macrophages and guides future therapeutic strategies development for ALF.